KEBIJAKAN ZONASI DALAM TIMBANGAN TEORI JUSTICE AS FAIRNESS JOHN RAWLS - Latifah, Nafsi; Nurmaini, Nurmaini; Putra, Muhammad Indra Eka; Hidayat, Hafiz; As Sayfullooh, Istiqomah (Fitrah, 2024)
In order to improve equitable access to education, the government implemented a zoning policy in the admission of new students from kindergarten to senior high school level. This research is conducted to explore the alignment between the zoning policy and the theory "Justice as Fairness" initiated by John Rawls. Literature study by reviewing various relevant reading materials is used as a method of this research. The results of this study include the alignment between the goal of equalizing education and Rawls' theory of justice. In addition, the policy's attention to economically disadvantaged students is also in line with Rawls' principle of justice, which prioritizes benefits to the most disadvantaged parties. Although this policy has a strong alignment with Rawls' theory of justice, its practice still causes many problems. In order to maximize the achievement of educational equity promoted by this policy, the government and all parties involved must always work together, and carry out this policy honestly, fairly, openly and critically.